Issues in Local Self-Government Reform in Russia - NANBA, Saria; ALIMOV, Emil (Journal of Advanced Research in Law and Economics, 2020)
The research is devoted to the constitutional legal regulation of local self-government in Russia. A study of democratic principles and established social relations allows authors to understand the state of local democracy in Russia and to assess the current situation from various points of view. An analysis of the local self-government reforms in Russia and budget policy will allow a better understanding of the further public and social development in Russia. The article analyzes the directions of legislative developments concerning local self-government in the Russian Federation, which sometimes have a multidirectional nature. Also, there are several issues raised in this article: doctrinal approaches and law-enforcement practice the constitutional foundations of local self-government, the competence of local authorities, the direct citizens’ participation in the conduct of local self-government and the local self-government financing. The authors conclude that current legal regulation of the local self-government can be referred to the mixed model. In the course of the study, the several deviations from the constitutionally established model of local self-government have been revealed.